Pengaruh Gaya Kepemimpinan, Budaya Organisasi, dan Komitmen Organisasi, Terhadap Kinerja Karyawan, di PT Perkebunan Nusantara IV Regional 1 PKS Rambutan - Alwandi, Abdul; Rindi Fatika Sari; Rusmewahni; Cia Cai Cen (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the effect of leadership style, organizational culture, and organizational commitment on employee performance at PT Perkebunan Nusantara IV Regional 1 PKS Rambutan. The approach used is quantitative with a survey method through distributing questionnaires to 58 processing section employees. The results showed that partially only organizational culture has a significant effect on employee performance, while leadership style and organizational commitment have no significant effect. But simultaneously, the three variables jointly affect employee performance. The coefficient of determination (Adjusted R²) of 0.560 indicates that 56% of the variation in employee performance can be explained by the three independent variables, while the rest is influenced by other factors outside the research model. This research confirms the importance of building a strong organizational culture as one of the main factors in improving employee performance.